PUBLIC SENTIMENT ON HEALTHCARE SERVICES DURING COVID-19 IN INDONESIA - Rumaisa, Fitrah; Muchsam, Yoki (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Covid-19 pandemic is an epidemic that makes all hospitals overwhelmed in handling patients. this of course affects the service of health workers to patients other than Covid-19 patients. Some opinions on these servants are conveyed on social media such as twitter. This article will describe public sentiment regarding health care services during the COVID-19 pandemic using Naive Bayes in Indonesia. The results of the analysis show that Indonesian citizens choose to be neutral towards the services of health workers in hospitals.